The effect of acids precipitants on the synthesis of WO3 hierarchical nanostructures for highly selective and sensitive H2S detection - Mpanza, Thokozani; Ogundipe, Sunday A.; Ndlangamandla, Ceboliyozakha L.; Swart, Hendrik C.; Nkosi, Steven S. (Frontiers in Sensors, 2023)
The detection and monitoring of H2S gas at high and lower concentrations is very crucial since this gas is highly toxic and can affect tissues and organs, especially in occupational environment. This work reports on the synthesis of WO3 nanostructures-based sensors for highly sensitive and selective H2S detection at low operating temperatures. These WO3 nanostructures were synthesized using pressurized hydrothermal process. Different acids from weak to strong (HNO3, H2SO4, and HCl) were employed as precipitants to form supposedly hierarchical and cube-like nanostructures of WO3. These WO3 nanostructures were characterized by XRD, SEM, TEM, XPS and BET analysis. The fabricated WO3 sensors were exposed to different target gases (CO2, H2, CH4, NH3, LPG and H2S) at different concentrations. They were found to be selective to H2S, and the WO3 precipitated by HCl otherwise referred to as WO3-HCl was found to be highly sensitive, with high response of S = 1394.04 towards 150 ppm of H2S at 125°C operating temperature. The WO3 precipitated by H2SO4 named WO3-H2SO4 showed a high response of 141.64 at 125°C operating temperature. Lastly, WO3 precipitated by HNO3 called WO3-HNO3, recorded a H2S response of 125.75 also at 125°C operating temperature. The HCl-precipitated WO3 is a promising candidate for selective detection of H2S, being the most sensitive in the series.